1022 Equivalent Management for All Fragility Fractures Occurring in The Older Patient. (12th October 2021) - Lenihan, J; Waseem, S; Rawal, J; Hull, P; Carrothers, A; Chou, D
Abstract: Aim: Neck of femur fractures (NOFs) are painful and occur in a vulnerable group of our population. Complications occur if their pain is under treated. Optimal management in the United Kingdom is governed by Best Practice Tariff (BPT). This was extended in 2020 without supporting published evidence to include all femur fractures (ROFs). We sought to compare PRPS for NOFs and ROFs throughout hospital admission. Method: We performed a retrospective matched analysis of all isolated osteoporotic ROFs to NOFs at our centre between 2018-2019. We analysed electronic patient records for relevant data. Matching criteria included Age +/- 2 years; cognition; walking aids; ASA; and social residence. Primary outcome measure was patient-reported pain scores (PRPS) at set time points. Secondary outcome measures were peripheral nerve blocks (PNB); patient controlled analgesia (PCA); time to surgery; anaesthetic type; length of stay (LOS); weightbearing status and 30-day mortality. Data was statistically analysed. Results: 11 ROFs were matched to 104 NOFs. There was no statistical difference between the two groups for age, sex, nor cognition and no difference in time to surgery; anaesthetic type; LOS; nor 30-day mortality. ROFs were more painful at all time points although not statistically significant. ROFs were more likely to have traction; PCA both pre- and post-operatively and not to weight bear. NOFs were more likely to have a PNB. Conclusions: ROFs are as painful if not more so than NOFs. Few ROFs receive PNB and require PCA. Better control of symptoms may improve outcomes. We support the extension of BPT.